Ontohedu: ontologia para educação patrimonial - Santos Júnior, Ramiro de Vasconcelos dos (Universidade Federal Rural do Semi-Árido, 2019)
Considering that the field of culture has undergone a process of computerization and that this dynamic has generated a large volume of data in the virtual environment, it becomes an important task to turn to the forms of circulation and appropriation of this information. Therefore, a study was carried out on Lajedo da Soledade, an archaeological site located in Soledade, Apodi district, Rio Grande do Norte. Through these studies, we collected inputs on heritage education, in which they were used to mapping the knowledge of Lajedo in order to support learning in the school and non-school field. In order to map the entire collection and make it freely available to the public (school and non-school), it was necessary to develop a technology capable of storing all the data, inferring them and later, through them, generating knowledge. In this way, this research presents an ontology called OntoHedu for the modeling of the archeological patrimony domain. Its specification was based on the knowledge extracted from the literature review and from the case study at the archaeological site. A Web application called WebHedu has been developed and integrated with OntoHedu to disseminate, share, search and retrieve information through its functionalities, serving as interface to the subjects who use it. The validation of the artifacts was carried out together with the specialists of the archaeological site through the acceptance model of technology TAM
Keywords: Ontologia; Educação Patrimonial; Patrimônio Arqueológico; Lajedo de Soledade; Ontology; Heritage Education; Archaeological Patrimony; Lajedo de Soledade; MULTIDISCIPLINAR::INTERDISCIPLINAR::COGNIÇÃO, TECNOLOGIAS E INSTITUIÇÕES